The Effect of Different Round Window Sealants on Cochlear Mechanics Over Time. Issue 8 (18th September 2021) - Mclean, Timothy; Clamp, Philip; Campbell, Luke; Hampson, Amy; Chambers, Scott; Collins, Aaron; Bester, Christofer; O'Leary, Stephen
Abstract : Background: This project investigated the effects of round window membrane (RWM) sealants after surgical incision, with a focus on audiological thresholds, ossicular mechanics, and the impact upon cochlear function and pathology. Methods: Twenty-eight guinea pigs were randomly allocated to one of three sealant groups (muscle, n = 7; fascia, n = 7, Tisseel, n = 8) or an unsealed control group (n = 6). Preoperative hearing was measured using auditory brainstem responses (ABRs). The ossicular chain and RWM were exposed surgically, and Laser Doppler Vibrometry (LDV) measurements were obtained from the long process of the incus. The RWM was incised then sealed (or left unsealed) according to group. ABR testing and LDV measurements were repeated 4 and 12 weeks after surgery. At 12 weeks all cochleae were harvested. Results: ABR thresholds deteriorated over time in all groups. Overall, group was not statistically significant ( p  = 0.064). There was no significant effect by group on LDV measurements ( p  = 0.798). Histopathological analyses of the RWM showed that the fascia group had more extensive fibrosis than other groups (Independent-Samples Median Test, p  = 0.001). However, there were minimal differences in the outer hair cell counts between the different intervention groups. Conclusions: All the interventions appeared to be safe while none affected the cochlear mechanics or hearing thresholds in a statistically significant manner.